Two case reports of renal-splenic disease presenting as renal tumors or metastases, with a literature review - Xu, Lijing; Wang, Jialin; Sun, Guangxi; Zeng, Hao (Frontiers in Oncology, 2025)
This article provides a comprehensive review of studies and case analyses on ectopic splenic tissue, with a particular focus on renosplenic disease. Ectopic splenic tissue refers to the abnormal non-physiological localization of spleen tissue, commonly resulting from splenic tissue implantation or hematogenous metastasis following splenectomy. Renosplenic disease is rare and often misdiagnosed as a renal tumor or tumor recurrence, which can lead to unnecessary surgical interventions. By discussing two cases of postoperative renosplenic disease in detail and combining them with a literature review, this article explores the pathogenesis, clinical presentation, imaging characteristics, and diagnostic methods of the condition. Analysis of 39 previously reported cases of nephrosplenopathy revealed that it predominantly affects male patients, typically occurs on the left side, and is often associated with a history of splenectomy, with lesions identified on average 20 years post-splenectomy. The clinical manifestations of nephroplenic disease are nonspecific and are mostly incidental findings during imaging examinations. Hybrid SPECT/CT and SPIO-enhanced MRI are considered the gold standards for diagnosing ectopic splenic tissue. However, the majority of cases are still confirmed through needle biopsy or surgical resection. While surgical diagnosis allows for lesion removal, it also carries risks of postoperative complications, such as intestinal fistula, as reported in one of the cases in this study. Research indicates that ectopic splenic tissue is generally benign but can cause symptoms by compressing adjacent structures. For asymptomatic patients, conservative management or active surveillance is a viable approach. However, in cases of large lesions, the decision between conservative treatment and surgical intervention should be carefully weighed. By summarizing 48 years of nephroplenic disease case data, this article aims to provide a clinical reference for the diagnosis and management of the condition. It emphasizes the critical role of imaging examinations and the potential for conservative treatment, aiming to reduce surgical risks and recovery times while improving diagnostic accuracy, treatment outcomes, and patients’ quality of life.